Heat Utilization in Boiler Plants by Using Liquid-Vapor Jet Apparatus - Serhii Sharapov; Jan Krmela; Danylo Husiev; Anton Verbytskiy; Jozef Bocko (Журнал інженерних наук)
The article solves the problem of heat utilization from combustion products in boiler plants. The proposed solution involves extracting heat to preheat the network water for the heating system and implementing additional heat utilization using a liquid-vapor jet apparatus. This will allow for additional working steam generation in the main steam generator and the unit based on the liquid-vapor jet apparatus. The article provides schemes and descriptions of traditional and proposed plants, indicating their design differences from the basic scheme. Comparative thermodynamic analysis of the proposed installation for additional recuperative heat utilization and the basic scheme is carried out, in which heat utilization occurs due to the extraction of heat from combustion products to preheat the network water of the heating system. As a result, the main thermodynamic parameters of the cycles of basic and proposed schemes are obtained, and the values of the capacities on the apparatuses included in these installations are determined. The energetic potential obtained from additional heat utilization is 8 %, which can be used for electricity generation. Exergy analysis assesses the efficiency of additional heat utilization in boiler plants using units based on liquid-vapor jet apparatus. As a result of the exergy analysis, the value of the exergetic efficiency of the scheme with additional heat utilization was obtained, which is 1.47 times higher than that of the basic scheme. A thermoeconomic analysis was performed to determine the cost values. Implementing the new scheme enables reducing the specific cost of the heating unit by 48 % and increasing the amount of steam generated in the installation by an additional 18 %.